Grumpy monkey - Lang, Suzanne; Lang, Max, 1982- (New York : Random House, 2018)
Jim Panzee wakes up in a bad mood one beautiful day, but he keeps denying he is grumpy even as his friends give advice for feeling better.
Keywords: Mood (Psychology) -- Fiction; Chimpanzees -- Fiction; Chimpanzees -- Juvenile fiction; Animals -- Juvenile fiction; Friendship -- Juvenile fiction; Animals -- Fiction; Friendship -- Fiction; Fiction; Juvenile works; Picture books